Functional Restoration of Bilateral Wrist Level Hand Amputee with Six-Toe Transfers and Three Free Flaps: An Alternative to Hand Allotransplantation or Prosthesis - Nehete, Rajendra; Nehete, Anita; Ghalme, Amol; Kulkarni, Abhishek; Fidvi, Al Iqyan (Indian Journal of Plastic Surgery, 2024)
Introduction Hand amputation at the wrist level is severely disabling, especially when bilateral. It is paramount to restore the hand function to the best possible level for the patient's daily living activities, as well as optimal social and occupational rehabilitation. There are various options for restoration of function after amputation at wrist and distal forearm levels including Krukenberg's operation, variations of toe transfers, hand allotransplantation, and prosthesis. Krukenberg's procedure and the reconstruction using toe transfer like Vilkki's procedure or two-toe transfers, restore only the pinch. Hand allotransplantation, although it gives excellent function, has limitations due to the complications of immunosuppression. Functional hand prosthesis, though superior in cosmetic appearance, have again limitations in function, and the cost is prohibitive for most patients in our country.Materials and Methods We present the unique case of a bilateral hand amputation at the wrist level reconstructed with three toes and free anterolateral thigh (ALT) flap in a single-stage surgery for each hand. In two stages, the patient had six toes transferred to both hands.Result All transferred toes and all three free (two ALT and one thoracodorsal artery perforator) flaps survived completely. Three-finger grip (tripod pinch) was thus restored in each hand. The hook grip was also restored well by the reconstructed two fingers. Within 3 months after surgery, the patient could perform all activities of daily living. He resumed his original job with some modification of his work within 6 months postinjury.Conclusion Hand reconstruction using three toes and a free flap is an excellent option for functional restoration for amputation at the wrist and distal forearm level. It allows an early return to function and good social and professional integration of the patient. This procedure is a potential alternative to expensive prosthesis and allotransplantation for a bilateral hand amputation.
Keywords: toe transfer; great toe; combined second and third toe; bilateral amputation; ALT flap; TDAP flap